As relações de poder na gestão da Escola Estadual Presidente Kennedy em Natal/RN: as ações decisórias dos órgãos colegiados - o conselho de escola e o caixa escolar - Morais, Pauleany Simões de (2012)
The present study examined the relations of power in the management of the Escola Estadual Presidente Kennedy, including the deliberate decisions on the School Council and School Fund, which guided the organization of the school. We sought to understand the management models that influenced the school organization, promoting contradictions in the decision making process. The school management is intensely marked by management models from the business logics as in the case of managerialism of bureaucracy. The formulation of educational policies based on managerialism has proposed a school-centered management with intense accountability of the school community in planning and monitoring the public services. The influences of these models subsidize hierarchical power relations that undermine the actions of decision-making of the collegiate bodies for the democratization of school management. To develop a research on the power, the investigation was based on studies of Bourdieu and Foucault. These authors understand the power in a relational system in a double sense, both in terms of discipline and the possibility of resistance. A theoreticalmethodological matrix was developed focusing on literature review, document analysis, structured interviews with twelve representatives of the segments belonging to the School Council and School Fund, as well as observations in meetings with the production of field notes. It was found that power relations experienced in the organization and activities of the school boards are marked by changes in public management over the years, promoting the contradictions between the concepts of corporate management originated in the business logics and the perspective of democratic management subsidized by official legislative documents at the national and state levels. The observations in meetings and analysis of the records showed that representatives related to management (president and manager of the school) have a privileged position with regard to exposure of their propositions, and are more likely to take a position in the political game of the collegiate bodies of work. It was also seen that the irregularity of meetings, particularly of the School Fund meetings, limits the experience of operation of the representatives in discussions concerning the planning and monitoring the actions of school management. Reports from representatives of the School Council showed that certain segments related to the management recognize their power of decision, however others have little interfere in the decision-making process in order to expound the desires of those who are represented by them. In the School Fund, the analysis of the records and interviews showed restricted moments of the meeting of representatives, and these only being aimed at choice or approval of the implementation plan prepared by the school management. The results showed no indications of moments of reflection to study the best chance for applicability of resources. This collegiate body (School Fund) has a questionable action when planning and monitoring the applicability of the financial resources of the School. To sum up, it was found that the Escola Estadual Presidente Kennedy still lives hierarchical power relations that undermine the institutionalization of democratic management in the various representative segments may take place in the game of political decision-making processes necessary for the organization of the school